Pengaruh Team Member Exchange, Komptensi terhadap Produktivitas Kerja dengan Kepuasan Kerja sebagai Variabel Intervening - Faiza, Garwa; Mujanah, Siti; Yanu Alif Fianto, Achmad; Suhardi, Suhardi (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
This research aims to analyses the influence of Team Member Exchange (TMX) and Competency on the Work Productivity of PT Techmicron Batam City with Job Satisfaction as an intervening variable. Data was collected from 100 employees of PT Techmicron Batam City using a questionnaire. The data analysis techniques used are multiple linear regression and Structural Equation Modelling (SEM). The research results show that Team Member Exchange (TMX) has a positive but not significant effect on Employee Work Productivity, Team Member Exchange (TMX) has a positive and significant effect on Job Satisfaction, Competency has a positive and significant effect on Employee Work Productivity, Competency has a positive and significant effect on Employee Job Satisfaction, Job Satisfaction has a positive and significant effect on the Work Productivity of PT Techmicron Batam City Employees. The implications of this research are the importance of compensation in building job satisfaction so that it can increase employee work productivity, as well as the importance of building Team Member Exchange (TMX) relationships in increasing employee job satisfaction.